2017
DOI: 10.1007/164_2017_49
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Trafficking of Gonadotropin Receptors in Health and Disease

Abstract: Gonadotropin receptors belong to the highly conserved subfamily of the G protein-coupled receptor (GPCR) superfamily, the so-called Rhodopsin-like family (class A), which is the largest class of GPCRs and currently a major drug target. Both the follicle-stimulating hormone receptor (FSHR) and the luteinizing hormone/chorionic gonadotropin hormone receptor (LHCGR) are mainly located in the gonads where they play key functions associated to essential reproductive functions. As any other protein, gonadotropin rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 226 publications
0
16
0
Order By: Relevance
“…Similar to other GPCRs, if the FSHR is not correctly folded the quality control surveillance of the proteosome removes the misfolded receptor. If properly folded, in the ER FSHR continues its transit to the Golgi and the PM ( 46 ). N-linked glycosylation (as well as disulfide bond formation) is a frequent feature of GPCRs that occurs during biosynthesis and facilitates folding of protein precursors by increasing their solubility, protecting from detrimental non-productive protein-protein interactions and stabilizing protein conformation ( 47 ).…”
Section: Domains and Motifs Involved In Fshr Upward Traffickingmentioning
confidence: 99%
“…Similar to other GPCRs, if the FSHR is not correctly folded the quality control surveillance of the proteosome removes the misfolded receptor. If properly folded, in the ER FSHR continues its transit to the Golgi and the PM ( 46 ). N-linked glycosylation (as well as disulfide bond formation) is a frequent feature of GPCRs that occurs during biosynthesis and facilitates folding of protein precursors by increasing their solubility, protecting from detrimental non-productive protein-protein interactions and stabilizing protein conformation ( 47 ).…”
Section: Domains and Motifs Involved In Fshr Upward Traffickingmentioning
confidence: 99%
“…In the case of the M3 mutant, which leads to hypergonadotropic primary amenorrhea [20], we found that replacement of aspartate with tyrosine at this position led to disruption of the interactions between TM helix 2 and helix 7 detected in the functional variants, with Y408 showing contacts with N380 of TM helix 1, S456 at TM helix 4, C584 at TM helix 6, and H615, N618, and N622 at TM helix 7, not exhibited by the WT I1 variant. The interhelical interactions disrupted in Y408 impacted on the receptor dynamics by reducing the conformational variability at the backbone level, which could be a feature recognized by the quality control system of the cell, thereby leading to intracellular trapping of the mutant receptor [21], a situation shared by M1. Map contacts in M1 and M2 mutants also evidenced the influence of the side chain atoms at position 408: a. Alanine side chain in M1 almost lost interaction with S619 at TM helix 7; and b.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations on the human FSHR have allowed identification of amino acid residues important for receptor function. For example, the loss-of-function, naturally occurring mutation D408Y found in patients with hypergonadotropic amenorrhea has been associated with intracellular trapping of the receptor probably due to misfolding and impaired upward traffic from the endoplasmic reticulum to the cell surface plasma membrane [20, 21]. Expression of the most common and best studied functional variants of the wild-type (WT) FSHR resulting from single nucleotide polymorphisms (SNP) with either alanine or threonine at position 307, and asparagine or serine at position 680 (which are expressed in strong linkage disequilibrium) also have been studied [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the anterior hypothalamus has been viewed as a “sleep center” since lesions in this area are known to cause long-lasting insomnia, whereas the posterior hypothalamus has been viewed as a “waking center” since its lesioning causes excessive sleepiness [see Saper et al ( 67 )]. Although this anterior-posterior classification of “sleep” vs. “waking” centers may be an oversimplification given the role other brain circuits ( 123 125 ), many of these historical insights still hold true today.…”
Section: The Lh In Energy Balance Behavioral State Transitions and Rmentioning
confidence: 99%